Flashcard Sentence As A Media For Increasing Elementary School Students' Literacy Understanding - Muhammad Ridho Adzani; Rahmad Salahuddin (Institut Agama Islam An-Nawawi Purworejo, 2022)
This study aims to find solutions to the challenges of learning to read difficulties for students who are at SDI Nurul Ulum Kab. Sumenep through interesting learning media in the form of Flashcard Sentence. The media is expected to be able to optimize the process of learning to read for elementary school students, as well as provide an understanding of what they read with media images related to the sentences read to increase students' literacy levels. This research uses Classroom Action Research (CAR) technique which goes through 3 cycles with each cycle containing 4 stages, namely planning, implementation, observation, reflection. After observing the Flashcard Sentence Learning Media, it can improve literacy understanding of SDI Nurul Ulum students by being shown when the Pre-action average score is 60.66 with a passing percentage of 0%, increasing in Cycle 1 the average score is 64.11 with a fixed passing percentage numbered 0%. After going through the evaluation process followed by cycle 2 getting an average score of 74.66 with a passing percentage of 55.56%, as the author's commitment at the beginning was that for a minimum graduation of 77.78% of the number of grade 2 students at SDI Nurul Ulum, cycle 3 was refined and giving an average score of 81.56 with a passing percentage of 100%.